Analysis of the Role and Current State of the Textile Industry in the Economy of Uzbekistan - Gulasal Ruzimboy Qizi , Madrakhimova (International Journal of Psychosocial Rehabilitation, 2020)
This article provides an analysis of the role and current state of the textile industry in the economy of Uzbekistan. Indeed, the processing industry in the world is seen as a major industrial sector that is important and vital to the development of a country’s economy. The strong processing sector of the industry represents the technological power of the country. Its decline or contraction is seen as a sign of economic decline. This, in turn, indicates that the processing industry is an important sector. So, this paper analyzes the current situation of the textile industry in the economy of Uzbekistan and gives a prediction for the future.